2014
DOI: 10.1021/ja500268w
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Hydroacylation of 1,3-Dienes by Cobalt Catalysis

Abstract: We describe a cobalt-catalyzed hydroacylation of 1,3-dienes with non-chelating aldehydes. Aromatic aldehydes provide 1,4-addition products as the major isomer, while aliphatic aldehydes favor 1,2-hydroacylation products. The kinetic profile supports an oxidative cyclization mechanism involving a cobaltacycle intermediate that undergoes transformation with high regio- and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 99 publications
2
80
0
Order By: Relevance
“…Switching to ferrocene-based ligands gave the desired β,γ-unsaturated product 3aa (entries 3–6). 22 Josiphos L1 provided the highest reactivity and regioselectivity (entry 5). Removing the backbone methyl group in Josiphos L1 resulted in a decrease in regioselectivity (entry 7 vs 5).…”
mentioning
confidence: 99%
“…Switching to ferrocene-based ligands gave the desired β,γ-unsaturated product 3aa (entries 3–6). 22 Josiphos L1 provided the highest reactivity and regioselectivity (entry 5). Removing the backbone methyl group in Josiphos L1 resulted in a decrease in regioselectivity (entry 7 vs 5).…”
mentioning
confidence: 99%
“…[1] Our laboratory has previously focused on the oxidation of aldehydes under Rh, Ru, and Co-catalysis. [2] Inspired by the promise of base metals, we considered that Ni-catalyzed cross-coupling of aldehydes could be classified into three general types: redox neutral, reductive, and oxidative (Figure 1). For example, Ogoshi's cross-coupling between two aldehydes is a redox neutral method that generates ester bonds.…”
mentioning
confidence: 99%
“…Experimentally, many transition metals have been reported to catalyze the intra-or inter-molecular hydroacylation, e.g. cobalt, 13,14 nickel, [15][16][17] copper, 18,19 ruthenium, [20][21][22][23][24][25] rhodium, [26][27][28][29][30][31] palladium, 32,33 iridium 34 and gold. 35 In 2007, Ryu et al reported the regioselective addition of aldehydes to enones catalyzed by the ruthenium hydride complex RuHCl(CO)(PPh 3 Þ 3 leading to 1, 3diketones.…”
Section: Introductionmentioning
confidence: 99%